Bacillus Calmette Guérin (BCG) activates lymphocyte to promote autophagy and apoptosis of gastric cancer MGC-803 cell - Yao, Keyu; Wang, Wei; Li, Haicheng; Lin, Jinfei; Tan, Weiguo; Chen, Yuhui; Guo, Lina; Lin, Dongzi; Chen, Tao; Zhou, Jie; Zhai, Shuangqing; Yu, Weiye (Cellular and Molecular Biology, 2018)
Bacillus Calmette Guérin (BCG) has a potential anti-tumor effect on gastric cancer. However, the mechanism is still unclear. In this study, we investigated the effect of BCG on gastric cancer cell line MGC-803 and studied the potential cooperation of BCG and lymphocyte in determining the final fate of cancer cells. After treatment with BCG, the cell viability was significantly inhibited in a dosage-dependent manner. Flow cytometry assay showed the apoptosis rates were significantly increased by BCG. Using western blot assay, results showed that BCG increased cleaved-caspase-3, LC-3BII and Atg-3. After cocultured with BCG and lymphocyte, the apoptosis rates, the levels of cleaved-caspase-3, and the protein levels of LC-3BII and Atg-3 were significantly increased compared with BCG or lymphocytes alone groups. ELISA detection found that BCG induced secretion of interferon gamma (IFNg) from lymphocytes. BCG with IFNg also increased levels of cleaved-caspase-3, LC-3BII and Atg-3. Taken together, BCG promotes lymphocyte immunocompetence to induce cell apoptosis and autophagy in MGC-803 cells, might through inducing release of IFNg from peripheral blood lymphocytes.